Acute effects of muscular fatigue on vertical jump performance in acrobatic gymnasts, evaluated by instrumented insoles: A pilot study - Martínez-Martí, F.; Latorre-Román, P. A.; Martínez-García, S.; Soto-Hermoso, V. M.; Carvajal, M. A.; López-Bedoya, J.; Palma, A. J. (Journal of Sensors, 2021)
The study of fatigue during training is becoming a very useful tool to avoid possible injuries not only during the training sessions but also during recovery time. Many researches have proved that concepts such as muscular fatigue and postactivation potentiation have a close relationship. With this aim, vertical jump can provide a very important information that can help to analyze the muscular fatigue that happened during this type of activity, mainly if the monitoring system is able to measure jumping parameters during their regular training session in their natural training environment. This study was performed with instrumented insoles called ECnsole. These insoles were tested with a group of twelve volunteers. In a tumbling surface, the participants performed a jumping protocol in three conditions: rest, fatigue-induced, and recovery. Using these validated insoles, the acrobatic gymnasts showed an inability to use the stretch-shortening cycle for improving vertical jumping performance after fatigue condition, although no deterioration of jump performance was found.